Interferon alpha promotes caspase-8 dependent ultraviolet light-mediated keratinocyte apoptosis via interferon regulatory factor 1 - Loftus, Shannon N.; Gharaee-Kermani, Mehrnaz; Xu, Bin; Moore, Tyson M.; Hannoudi, Andrew; Mallbris, Mischa J.; Klein, Benjamin; Gudjonsson, Johann E.; Kahlenberg, J. Michelle (Frontiers in Immunology, 2024)
Introduction Ultraviolet (UV) light is a known trigger of both cutaneous and systemic disease manifestations in lupus patients. Lupus skin has elevated expression of type I interferons (IFNs) that promote increased keratinocyte (KC) death after UV exposure. The mechanisms by which KC cell death is increased by type I IFNs are unknown. Methods Here, we examine the specific cell death pathways that are activated in KCs by type I IFN priming and UVB exposure using a variety of pharmacological and genetic approaches. Mice that overexpress Ifnk in the epidermis were exposed to UVB light and cell death was measured. RNA-sequencing from IFN-treated KCs was analyzed to identify candidate genes for further analysis that could drive enhanced cell death responses after UVB exposure. Results We identify enhanced activation of caspase-8 dependent apoptosis, but not other cell death pathways, in type I IFN and UVB-exposed KCs. In vivo, overexpression of epidermal Ifnk resulted in increased apoptosis in murine skin after UVB treatment. This increase in KC apoptosis was not dependent on known death ligands but rather dependent on type I IFN-upregulation of interferon regulatory factor 1 (IRF1). Discussion These data suggest that enhanced sensitivity to UV light exhibited by lupus patients results from type I IFN priming of KCs that drives IRF1 expression resulting in caspase-8 activation and increased apoptosis after minimal exposures to UVB.